Integration of energy and seismic-structural design variables through the optimization of a multi-story residential light-frame timber building with different seismic lateral connectors and building stories. (1st October 2022) - Wenzel, Alexander; Vera, Sergio; Guindos, Pablo
Abstract: The structural and energy performance of the light-frame buildings is intrinsically linked, but the design process of both domains is not. Light-frame timber buildings are subjected to overheating due to the lack of thermal mass. A solution to eliminate or mitigate overheating is adding thermal mass, but the main drawback is increasing the seismic forces the building needs to withstand. Furthermore, the length of exterior shearwalls, fenestration openings, and studs spacing affect both the energy and structural performances. This paper aims to analyze and integrate energy and seismic-structural design variables for a light-frame residential timber building with different lateral seismic connectors and building stories. An Energy and Structural Timber Building Optimization (ESTIBO) methodology is proposed to integrate energy and seismic-structural design variables by optimizing the building energy performance. ESTIBO is based on GenOpt optimization software using a hybrid multidimensional optimization algorithm, while the energy simulations are performed on EnergyPlus using the Rhino's Grasshopper plugin. A structural model is implemented in Matlab under a modal response analysis of the building structure. The main results show that integrating critical design variables achieves different optimal values considering feasible structural solutions with reduced heating and cooling loads. It was found the four main variables that primarily reflect the link between energy and seismic-structural performances are stud spacing, wall insulation thickness, wall insulation type (high or low specific heat capacity), and floor concrete layer thickness. This paper contributes to improving the understanding of light-frame timber buildings' performance regarding the interaction of energy and structural-seismic design variables. Moreover, ESTIBO demonstrated to be able to provide optimal energy and seismic-structural solutions. Thus, it can support the early design stage of light-frame timber buildings. Highlights: A novel ESTIBO method is applied to integrate energy and structural design variables. Structural and energy behavior are tightly coupled for light-frame timber buildings. Wall insulation, concrete floor and stud spacing are strongly linked. Seismic capacity strongly restraints the optimal energy design for timber buildings. ESTIBO found optimal designs by 250–450 simulations for a 9.06 × 10 7 design space.